Efficient Monolithic Perovskite/Perovskite Tandem Solar Cells. Issue 8 (14th December 2016) - Forgács, Dávid; Gil‐Escrig, Lidón; Pérez‐Del‐Rey, Daniel; Momblona, Cristina; Werner, Jérémie; Niesen, Bjoern; Ballif, Christophe; Sessolo, Michele; Bolink, Henk J.
Abstract : Efficient monolithic perovskite/perovskite tandem solar cells are fabricated using two perovskite absorbers with complementary bandgaps. By employing doped organic semiconductors, an efficient and selective extraction of the charge carriers is ensured. This study demonstrates perovskite/perovskite tandem cells delivering a maximum efficiency of 18%, highlighting the potential of vacuum‐deposited multilayer structures in overcoming the efficiency of single‐junction perovskite devices.